Deriving Moral Considerability from Leopold's A Sand County Almanac. Issue 2 (3rd May 2016) - Dixon, Ben
Abstract: I argue that a reasonable understanding of Leopold's 'Land Ethic' is one that identifies possession of health as being a sufficient condition for moral consideration. With this, Leopold extends morality not only to biotic wholes, but to individual organisms, as both can have their health undermined. My argument centers on explaining why Leopold thinks it reasonable to analogize ecosystems both to an organism and to a community: both have a health. My conclusions undermine J. Baird Callicott's rhetorical dismissal of the organism analogy's importance, a dismissal crucially serving his thesis that Leopoldians should hold community membership necessary for moral standing.